Alcalóides isoquinolínicos e atividade ansiolítica de três espécies do gênero Griffinia (Amaryllidaceae) - Leite, Elder Luis Lima (2023)
Griffinia gardneriana (Herb.) Ravenna, Griffinia liboniana Morren and Griffinia nocturna Ravenna (Amarillydaceae) are easy-to-grow bulbous plants found in the Northeast and Southeast regions of Brazil, where they are commonly used for ornamental purposes. The chemical study of the genus Griffinia is still incipient or even non-existent, as in the case of G. liboniana. The Amarillydaceae family is characterized by the occurrence of unique isoquinoline alkaloids, which have diverse pharmacological activities. This work aimed to determine the alkaloid profile of Griffinia spp. bulbs and evaluate anxiolytic activity of the alkaloid fractions. The studied plants were grown in cultivation houses at Embrapa Agroindústria Tropical. The dried and ground bulbs were defatted with hexane in an ultrasonic bath and then subjected to an acidic-basic liquid-liquid partition sequence, resulting in alkaloid fractions that were later confirmed by gas chromatography coupled to mass spectrometry (GC-MS). Anxiolytic activity was evaluated in zebrafish (Danio rerio) through intraperitoneal (i.p.) injection at doses of 40, 100 and 200 mg/kg each, using diazepam (40 mg/kg) as a positive control and 3% DMSO (group control – drug diluent) in light-dark box test. GC-MS analyses revealed 23 isoquinoline alkaloids belonging to lycorine, homolycorine, galanthamine, crinine, haemanthamine, montanine and narcisclasine-type skeletons. The chemical profiles were relatively similar, being 13 compounds common to the three species. The major component for G. gardneriana and G. liboniana was lycorine, while anhydrolycorine was the main compound for G. noctuna. The alkaloids 11,12-dehydro-2- methoxyanhydrolycorine and 11,12-dehydro-2-hydroxyanhydrolycorine are being reported for the first time to the best of our knowledge. Alkaloid extracts from the three species of Griffinia spp. demonstrated anxiolytic effect. Pre-treatment with diazepam (40 mg/kg) and pizotifen (32 mg/kg) was able to reverse the anxiolytic action, indicating the involvement of the GABAergic and serotonergic systems. Molecular docking showed that the compounds vittatine, lycorine and 11,12-dehydro-2- methoxyassoanine have good affinity both with 5-HTR and human GABA receptors, suggesting these compounds as responsible for the anxiolytic effect.